Hemoglobin Sunshine Seth: A Case Report of Low-Oxygen-Affinity Hemoglobinopathy - Leah S. Heidenreich; Jennifer L. Oliveira; Peter J. Holmberg; Vilmarie Rodriguez (Case Reports in Pediatrics)
Pulse oximetry is routinely used in the newborn nursery for clinical monitoring and to detect critical congenital heart disease. The differential diagnoses for reduced peripheral oxygen saturation in an infant include congenital heart disease, respiratory distress syndrome, transient tachypnea of the newborn, persistent pulmonary hypertension of the newborn, meconium aspiration syndrome, pneumonia, pneumothorax, and sepsis. The diagnostic evaluation for neonatal hypoxemia can be invasive and expensive. When this evaluation is unrevealing, other interventions may be tried without clear benefit to the patient, including, but not limited to, supplemental oxygen. Therefore, it is important to consider alternative, albeit rare, diagnoses, including hemoglobinopathies with abnormal oxygen binding properties. Mutations in the structure of alpha- and beta-globin chains can alter the affinity of hemoglobin for oxygen, and changes in oxygen affinity may result in changes in the oxygen saturation detected by pulse oximetry. These changes may or may not be of clinical significance. This case report describes Hemoglobin Sunshine Seth, a rare low-oxygen-affinity hemoglobin variant presenting as reduced peripheral oxygen saturation in an otherwise well-appearing infant male.